KEPUASAN KERJA PEGAWAI DI TINJAU DARI KEMAMPUAN, KOMPENSASI, BEBAN KERJA DAN PENEMPATAN KERJA PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MEDAN - Andini, Aulia; Hermansyur, Hermansyur; Pitono, Pitono (Cattleya Darmaya Fortuna, 2025)
This research aims to analyze the influence of ability, compensation, workload and work placement on employee job satisfaction, both partially and simultaneously. The total population in this study was 109 people, and by using saturated sampling techniques a sample of 109 people was obtained. The analysis technique used is multiple linear Regression. The results of the research show that ability has no effect on employee job satisfaction at the Medan City Investment and One Stop Integrated Services Agency, compensation has a Positive and significant effect on employee job satisfaction at the Medan City One Stop Investment and Integrated Services Agency, workload has a Positive and significant effect on employee job satisfaction at the Medan City Investment and One Stop Integrated Services Agency and job placement has a Positive and significant effect on employee job satisfaction at the Medan City One Stop Investment and Integrated Services Agency. Simultaneously shows that ability, compensation, workload and work placement have a Positive and significant effect on employee job satisfaction at the Medan City Investment and One Stop Integrated Services Agency.